Unemployment insurance financing : an evaluation - Becker, Joseph M. (Washington, D.C. : American Enterprise Institute, 1981)
This book re-examines two basic financing decisions made by the designers of the Unemployment Insurance System: to make each state as well as each employer responsible for their costs. It concludes that these decisions were wise and have contributed to the system's overall success.
Includes bibliographical references.
rpm 03/04/2018
Loans
Keywords: Unemployment insurance